PENGARUH MODEL PEMBELAJARAN PJBL TERHADAP PROFIL PELAJAR PANCASILA PESERTA DIDIK SDK PENABUR KOTA WISATA - Nababan, tiurma; Ristanto, Rizhal Hendi; Hakim, Lukman El (Bahasa Indonesia Prima, 2024)
Research describes the experiences of teachers and students in implementing the influence of the Project-Based Learning (PjBL) model on the Pancasila student profile at SDK PENABUR Kota Wisata. The research employs a qualitative approach with a case study method. Data collection techniques were conducted through interviews. The analysis of student interview results indicates that students have experiences such as: (1) Students are required to be more creative so that the projects they produce can be interesting. (2) Learning with the PjBL model demands that students not only be creative but also innovative in producing a project. (3) Strengthening the values of togetherness with friends, as project work is carried out in groups. Meanwhile, the analysis of teacher interview results provides insights such as: (1) Teachers are greatly helped in exploring students' soft skills. (2) The PjBL model guides teachers to bring students into learning experiences that are relevant to their daily lives, making the learning very meaningful for both students and teachers. (3) Differences in character among students sometimes require students and teachers to work synergistically so that each group can enjoy the learning process. (4) The diverse levels of IQ and EQ among students demand that teachers, students, and parents work together to ensure the learning process runs well.